Antibiotic Production by Erwinia herbicola Eh1087: Its Role in Inhibition of Erwinia amylovora and Partial Characterization of Antibiotic Biosynthesis Genes - Kearns, L. P. (American Society for Microbiology, 1998)
Mutants of Erwinia herbicola Eh1087 (Ant(−)), which did not produce antibiotic activity against Erwinia amylovora, the fire blight pathogen, were selected after TnphoA mutagenesis. In immature pear fruit Ant(−) mutants grew at the same rate as wild-type strain Eh1087 but did not suppress development of the disease caused by E. amylovora. These results indicated that antibiosis plays an important role in the suppression of disease by strain Eh1087. All of the Ant(−) mutations obtained were located in a 2.2-kb region on a 200-kb indigenous plasmid. Sequence analysis of the mutated DNA region resulted in identification of six open reading frames, designated ORF1 through ORF6, four of which were essential to antibiotic expression. One gene was identified as a gene which encodes a translocase protein which is probably involved in antibiotic secretion. A sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis of plasmid proteins produced in Escherichia coli minicells confirmed the presence of proteins whose sizes corresponded to the sizes of the predicted open reading frame products.